QMRA of Ralstonia solanacearum in potato cultivation: Risks associated with irrigation water recycled through managed aquifer recharge - Carina Eisfeld; Boris M. van Breukelen; Gertjan Medema; Jan M. van der Wolf; Jouke Velstra; Jack F. Schijven (Science of The Total Environment, 2023)

Prevention of well clogging during aquifer storage of turbid tile drainage water rich in dissolved organic carbon and nutrients - Emiel Kruisdijk; Julian F. Ros; Devanita Ghosh; Maren Brehme; Pieter J. Stuyfzand; Boris M. van Breukelen (Hydrogeology Journal, 2023)
Well clogging was studied at an aquifer storage transfer and recovery (ASTR) site used to secure freshwater supply for a flower bulb farm. Tile drainage water (TDW) was collected from a 10-ha parcel, stored in a sandy brackish coastal aquifer via well injection in wet periods, and reused during dry periods. This ASTR application has been susceptible to clogging, as the TDW composition largely exceeded most clogging mitigation guidelines. TDW pretreatment by sand filtration did not cause substantial clogging at a smaller ASR site (2 ha) at the same farm. In the current (10 ha) system, sand filtration was substituted by 40-μm disc filters to lower costs (by 10,000–30,000 Euro) and reduce space (by 50–100 m 2 ). This measure treated TDW insufficiently and injection wells rapidly clogged. Chemical, biological, and physical clogging occurred, as observed from elemental, organic carbon, 16S rRNA, and grain-size distribution analyses of the clogging material. Physical clogging by particles was the main cause, based on the strong relation between injected turbidity load and normalized well injectivity. Periodical backflushing of injection wells improved operation, although the disc filters clogged when the turbidity increased (up to 165 NTU) during a severe rainfall event (44 mm in 3 days). Automated periodical backflushing, together with regulating the maximum turbidity (<20 NTU) of the TDW, protected ASTR operation, but reduced the injected TDW volume by ~20–25%. The studied clogging-prevention measures collectively are only viable as an alternative for sand filtration when the injected volume remains sufficient to secure the farmer’s needs for irrigation.

Ecological control analysis: being(s) in control of mass flux and metabolite concentrations in anaerobic degradation processes - Wilfred F. M. Röling; Boris M. Van Breukelen; Frank J. Bruggeman; Hans V. Westerhoff (Environmental Microbiology, 2007)
Summary Identification of the functional groups of microorganisms that are predominantly in control of fluxes through, and concentrations in, microbial networks would benefit microbial ecology and environmental biotechnology: the properties of those controlling microorganisms could be studied or monitored specifically or their activity could be modulated in attempts to manipulate the behaviour of such networks. Herein we present ecological control analysis (ECA) as a versatile mathematical framework that allows for the quantification of the control of each functional group in a microbial network on its process rates and concentrations of intermediates. In contrast to current views, we show that rates of flow of matter are not always limited by a single functional group; rather flux control can be distributed over several groups. Also, control over intermediate concentrations is always shared. Because of indirect interactions, through other functional groups, the concentration of an intermediate can also be controlled by functional groups not producing or consuming it. Ecological control analysis is illustrated by a case study on the anaerobic degradation of organic matter, using experimental data obtained from the literature. During anaerobic degradation, fermenting microorganisms interact with terminal electron‐accepting microorganisms (e.g. halorespirers, methanogens). The analysis indicates that flux control mainly resides with fermenting microorganisms, but can shift to the terminal electron‐accepting microorganisms under less favourable redox conditions. Paradoxically, halorespiring microorganisms do not control the rate of perchloroethylene and trichloroethylene degradation even though they catalyse those processes themselves.

Reversible depression of transcription during hibernation - F. van Breukelen; Martin S. (Journal of Comparative Physiology B, 2002)

Ubiquitin conjugate dynamics in the gut and liver of hibernating ground squirrels - F. van Breukelen; Carey H. (Journal of Comparative Physiology B, 2002)

Characterization of ATP-dependent proteolysis in embryos of the brine shrimp, Artemia franciscana - F. van Breukelen; S. C. Hand (Journal of Comparative Physiology B, 2000)

Fate and effects of the insecticide Dursban® 4E in indoor Elodea-dominated and macrophyte-free freshwater model ecosystems: II. Secondary effects on community structure - T. C. M. Brock; M. van den Bogaert; A. R. Bos; S. W. F. van Breukelen; R. Reiche; J. Terwoert; R. E. M. Suykerbuyk; R. M. M. Roijackers (Archives of Environmental Contamination and Toxicology, 1992)